Determinasi sosial ekonomi terhadap kemiskinan di Jawa Timur: Analisis data panel menggunakan fixed effect model - Oktavia, Sinta; Febriani, Reva Ghani; Hadi, Muhammad Abdul; Asykurunnizza, Anindya Zulfa; Adyistia, Rintan Della (Journal of Economics Research and Policy Studies, 2025)
Poverty is one of the main challenges facing East Java, as it is the most densely populated region in Indonesia. This study aims to investigate the impact of social and economic variables, including life expectancy, population size, gross domestic product per capita, human development index, labour force participation rate, and minimum wage, on the poverty rate in East Java Province from 2021 to 2023. This research employs a quantitative method to collect panel data from 38 districts/cities, analysed using a panel data regression model with the Fixed Effects Model (FEM). The results indicate that Life Expectancy, Population Size, and GDP per capita have a negative and significant impact on poverty, meaning that increases in these three variables can reduce poverty levels. Meanwhile, the Human Development Index, Labour Force Participation Rate, and Minimum Wage have a positive but insignificant impact, suggesting that these factors are not yet effective in reducing poverty. These findings indicate that health development policies, management of the productive-age population, and inclusive economic growth have a greater impact on poverty alleviation than increases in the minimum wage or HDI. The government should focus on data-driven interventions, such as health programs and workforce training, and ensure the equitable distribution of development benefits.